Prenatal Considerations and Outcomes for Girls Aged 14 and Under: Development of a Multidisciplinary Team in a Large Tertiary Care Facility. (17th June 2022) - Fairchild, Esther; Kyle, Sara; Marion, Shirley; Cheatham, Allyson; Lecky, Tashein; Harris, Shalawn; Jensen, Sarah
Abstract : Introduction: Adolescent girls account for 11% of all births that occur globally every year. Among developing countries, the United States continues to have one of the highest adolescent birth rates, despite a decreasing trend between 1990 and 2010. Pregnant adolescents are a vulnerable population who are at increased risk for maternal morbidity and mortality. Additional risks are noted within the early adolescent population, usually defined as age 10 to 14. Process: At Parkland hospital, a large tertiary care facility in Dallas, Texas, a multidisciplinary team was created in 2017 to care for this vulnerable population. The team consisted of a certified nurse‐midwife (CNM), a Certified Child Life Specialist, a maternal fetal medicine physician, a social worker, and a Spanish interpreter, with additional services consulted as needed. Between 2017 and 2020, this team grew to include 8 CNMs and provided care to 76 young adolescents ages 14 and younger. Outcomes: Of the young adolescents who attended prenatal visits with the Adolescent Prenatal Care Team at Parkland, 87% presented to Parkland for birth. Eighteen percent had pregnancy‐induced hypertension or eclampsia. Only 7% of adolescents in the program gave birth prior to 37 weeks. Seventy‐four percent had vaginal births. Sixty percent of the adolescents attended known postpartum visits. Discussion: In contrast to most studies, this Adolescent Care Team did not find a high rate of premature birth in early adolescents. Further work by this team is needed to compare the data obtained during this period with data on similar adolescents who have given birth at Parkland in prior years. In addition, comparing outcomes of early adolescents with those aged 15 to 19, who were not included in the Adolescent Care Team, will help to understand the impact that such a team or similar intervention might have on this vulnerable population.